Increasing capacity for wireless communication systems based on signal waveform collaboration - Jun SHI; Xue-jun SHA; Qin-yu ZHANG; Xiao-cheng SONG; Nai-tong ZHANG (Tongxin xuebao)
A wireless communication technology based on signal waveform collaboration was proposed for resolving the conflict between limited spectrum resources and the rapidly growing service needs.The proposed technology employs linear frequency modulation (LFM) signals to transmit different users' information by utilizing the dual relationship between the energy concentration property of sinusoidal signals and that of LFM signals in the frequency and fractional domains,and the transmitted signals are superimposed on communication waveforms of the traditional sinusoidal carrier communication system on the same frequency band.At the receiver,frequency-and fractional-domain filters are applied to separate two kinds of users' signals.Moreover,the system model of the proposed technology is constructed,and theoretical analysis is also derived.The validity of the theoretical derivations is demonstrated via simulations.It has been shown that spectral efficiency can be effectively improved using signal waveform collaboration and transform-domain filtering.Theoretically,the proposed technology can achieve twice system capacity as large as that of the traditional sinusoidal carrier communication system.